Educational attainment trajectories among female offenders: An administrative data linkage study. - Coles, Christabel; Dickson, Hannah; Blackwood, Nigel; Wickersham, Alice (International Journal of Population Data Science, 2025)
Objectives Female offending carries significant social and economic costs, which could be mitigated by early interventions prior to offending onset. Educational attainment has been associated with offending however, limited research investigates changes in educational attainment and how these correspond to patterns of re-offending across the lifespan in females. Methods We investigated this using UK administrative data from the linked Police National Computer and National Pupil Database. Educational attainment scores were available at Key Stage 1 (5-7 years), Key Stage 2 (7-11 years), and Key Stage 4 (14-16 years). Scores were standardised according to average attainment at each academic year. Linear mixed models were used to investigate how educational attainment trajectories were impacted by (1) gender, (2) offender status (offender/non-offender [females-only]), and (3) re-offending trajectory membership (females-only). Analyses controlled for Ethnicity and free school meal eligibility. Results In my talk, I will share findings on the differences in educational attainment trajectories from Key Stages 1 to 4 between males and females, female offenders and non-offenders, and amongst females following distinct trajectories of re-offending. Conclusion Findings may inform education and criminal justice system responses to youth offending behaviour in females. If females following distinct re-offending trajectories show distinct patterns of educational attainment, we may be able to identify at-risk students who are in need of additional support or interventions.